Efficient Technology for Increasing the Efficiency of Small Scale Capture Fisheries Effort, A Review - Adi Susanto (Jurnal Perikanan dan Kelautan, 2011)
The potential fisheries in Indonesia has been used by the community in various ways and scale. Most of the existing fishing effort is a small-scale business with a variety of problems faced including the increase in cost, aquatic environment degradation, decline in the catch as well as problems related to non-targeted fishes. In order to overcome these problems required an Appropriate Technology so that the small-scale fishing enterprises can continue to evolve. Types of appropriate technology or so called TTG, which can be adopted to improve the efficiency of small-scale fishing enterprises, namely: attractor squid, deep-sea traps, and fish meat bone separator "Suritech ™". The presence of TTG is expected to provide added value both in economic, ecological and sustainability of fishery resources so that sustainable fisheries can be realized and felt by all walks of life